Réponses

  • Omnes
  • Modérateur confirmé
2014-03-04T22:13:07+01:00
Salut

(a-1)² + (a+1)² = a² - 2a + 1 + a² + 2a + 1 = 2a² +2.
2(a² +1) = 2a² + 2

donc (a-1)² + (a+1)² = 2(a² +1)




(a-1)² + (a+1)² =2(a²+1)
(a-1)² + (a+1)² :
De la forme (A-B)²+(A+B)² :
(a²-2a+1)+(a²+2a+1) = a²-2a+1+a²+2a+1 = (2a²+2) = 2(a²+1)
voilà jespère que sa ta aidé :)
2014-03-04T22:18:37+01:00
Vérifier que :
(a - 1)² + (a + 1)² = 2 (a² + 1)

= (a - 1)² + (a + 1)² = a² - 2a + 1 + a² + 2a + 1 = 2a² + 2
= 2 (a² + 1) = 2a² + 2

(a - 1)² + (a + 1)² = 2 (a² + 1)
est donc vérifié